Solving dynamic economic dispatch problem with security constraints using bacterial foraging PSO-DE algorithm - Vaisakh, K.; Praveena, P.; Rama Mohana Rao, S.; Meah, Kala (International journal of electrical power & energy systems, 2012)
► We present a heuristic hybrid optimization methodology, namely, Bacterial foraging PSO-DE (BPSO-DE) algorithm. ► We integrate three algorithms such as BFOA, PSO and DE to form hybrid methodology. ► The incorporated PSO and DE operators in BFOA algorithm eliminates the problem of stagnation of solution. ► The global solution is achieved by selecting the bacterium with good foraging strategies with the PSO/DE operators. This paper presents a heuristic optimization methodology, namely, Bacterial foraging PSO-DE (BPSO-DE) algorithm by integrating Bacterial Foraging Optimization Algorithm (BFOA), Particle Swarm Optimization (PSO) and Differential Evolution (DE) for solving non-smooth non-convex Dynamic Economic Dispatch (DED) problem. The DED problem exhibits non-smooth, non-convex nature due to valve-point loading effects, ramp rate limits, spinning reserve capacity, prohibited operating zones and security constraints. The proposed hybrid method eliminates the problem of stagnation of solution with the incorporated PSO and DE operators in original bacterial foraging algorithm. It achieves global cost by selecting the bacterium with good foraging strategies. The bacteria with good foraging strategies are obtained in the updating process of every chemo-tactic step by the PSO operator. The DE operator fine tunes the solution obtained through bacterial foraging and PSO operator. A 3- and 7-unit systems for static economic dispatch, a 26-bus, 6-generator test system and an IEEE 39-bus, 10-unit New England test systems are considered to show the effectiveness of the proposed method over other methods reported in the literature.